Perioperative Management in Patients With Cleft Lip and Palate - Preidl, Raimund; Kesting, Marco Rainer; Rau, Andrea (Journal of Craniofacial Surgery, 2020)
In cleft care, perioperative treatment strategies like ear nose and throat (ENT) diagnostics as well as postoperative antibiotics, feeding, and duration of inpatient stay are nonstandardized procedures varying between different centers. Likewise, intraoperative choice of suture materials and time of suture removal are performed inconsistently. Therefore, we wanted to collect information on protocols focusing on these topics to summarize and subsume currently approved treatment strategies of centers around the world. We ask members of international cleft centers for their respective treatment strategies and performed descriptive statistics.Absorbable suture material is used for reconstruction of the outer lip skin in 20 of 70 centers. Removal of skin sutures is conducted after 7.0 ± 1.5 days. Suturing of the orbicularis oris muscle, the enoral and nasal mucosa, as well as the palatal musculature is predominantly performed with absorbable suture materials. Intraoperative antibiotic prophylaxis is applied in 82.9% of the participating centers. In contrast, 31.9% of the departments do not apply any antibiotic postoperatively. Postoperative feeding is performed in 27 centers via a nasogastric tube for 4.6 ± 2.3 days on average. Mean length of postoperative inpatient stay is 4.1 ± 2.6 days in children after cleft lip surgery and 4.5 ± 2.7 days after cleft palate surgery. ENT consultation before surgery is routinely conducted in 52.8% of the centers and 82.9% of ENT colleagues investigate middle ear pathologies in the same operation in which cleft repair is performed.Closure of the lip skin is predominantly performed with nonabsorbable suture material followed by a suture removal after 1 week. Intraoperative antibiotic prophylaxis as well as inpatient hospital stay of 4 to 5 days in combination with oral feeding and a preoperative consultation and intraoperative cooperation with the ENT department seems to be well-proven concepts in cleft lip palate patient care. However, this analysis illustrated the variations and differing approaches in perioperative care emphasizing the need to verify perioperative management concepts in cleft surgery-preferably in the context of multicenter studies.
CRIS-Team Scopus Importer:2020-01-10